Strategi Menumbuhkan Karakter Anak Melalui Teknologi Digital - Ruchiyat, Marina Gusnia; Kurniawan, Mirdan; Triyaningsih, Triyaningsih; Marwan, Marwan; Prihatmojo, Agung (Information Technology Education Department, 2024)
Character development is a crucial aspect to instill in children amidst the rapid advancement of technology. The importance of shaping character with digital technology is a significant preventive step to keep children away from the possibility of a character value crisis that can arise due to the influence of technology that continues to grow. The use of digital technology can be directed positively to support children's character building. This article aims to identify and explore strategies that can be implemented to build children's character through the use of digital technology. The research method used is a descriptive qualitative method with a literature review approach. The literature sources involved books, journals and scientific articles as the main focus of the research. This approach provides a strong theoretical foundation to formulate effective strategies in the context of character education and digital technology. The analysis of this study found digital technology-based character education strategies used by teachers, schools and parents. The findings in this article provide a comprehensive strategy on the implementation of character education through digital technology that involves the important roles of teachers, schools and parents.